2021
DOI: 10.4081/hr.2021.9215
|View full text |Cite
|
Sign up to set email alerts
|

Lysine-Specific Histone Demethylase 1 Inhibition Enhances Robust Fetal Hemoglobin Induction in Human β0-Thalassemia/Hemoglobin E Rrythroid Cells

Abstract: Induction of fetal hemoglobin (HbF) ameliorates the clinical severity of β-thalassemias. Histone methyltransferase LSD1 enzyme removes methyl groups from the activating chromatin mark histone 3 lysine 4 at silenced genes, including the γ-globin genes. LSD1 inhibitor RN-1 induces HbF levels in cultured human erythroid cells. Here, the HbF-inducing activity of RN-1 was investigated in erythroid progenitor cells derived from β0-thalassemia/HbE patients. The significant and reproducible increases in γ-globin trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…At a concentration of 0.004 uM, RN-1 significantly increased the expression of γ-globin mRNA and HbF expression without any significant toxicity and regardless of HbF baseline levels [113]. Transcript levels of numerous key γ-globin repressors and co-repressors such as NCOR1, SOX6 and MYB were also modulated by RN-1 treatment [113]. Collectively, these data suggest the consideration of RN-1 for further development as an additional strategy to induce HbF in both SCD and thalassemic syndromes.…”
Section: Lysine-specific Histone Demethylase 1 (Lsd1) Inhibitorsmentioning
confidence: 93%
See 2 more Smart Citations
“…At a concentration of 0.004 uM, RN-1 significantly increased the expression of γ-globin mRNA and HbF expression without any significant toxicity and regardless of HbF baseline levels [113]. Transcript levels of numerous key γ-globin repressors and co-repressors such as NCOR1, SOX6 and MYB were also modulated by RN-1 treatment [113]. Collectively, these data suggest the consideration of RN-1 for further development as an additional strategy to induce HbF in both SCD and thalassemic syndromes.…”
Section: Lysine-specific Histone Demethylase 1 (Lsd1) Inhibitorsmentioning
confidence: 93%
“…When tranylcypromine (TCP) and RN-1 were tested in primate and murine erythroid cell cultures, RN-1 was shown to induce F cells and γ-globin mRNA at much greater levels than either TCP or HU [112]. More recently, the use of RN-1 was investigated in erythroid progenitor cells derived from β0-thalassemia/HbE patients [113]. At a concentration of 0.004 uM, RN-1 significantly increased the expression of γ-globin mRNA and HbF expression without any significant toxicity and regardless of HbF baseline levels [113].…”
Section: Lysine-specific Histone Demethylase 1 (Lsd1) Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various pharmacological inhibitors targeting HDACs, DNMT1, LSD1, and G9A increase -globin expression in different experimental model systems and some of have advanced to clinical trials [12][13][14]. LSD1 inhibitors are particularly potent HbF activators and promising therapeutic agents as shown by studies in primary erythroid cell cultures derived from normal [15] and  o -thalassemia/HbE patients [16], sickle cell disease mouse models [17][18][19] and baboons [20][21][22], but detailed knowledge of their mechanism of action has not been established. Our previous studies showed that the LSD1 inhibitor RN-1 administration stimulated impressive increases in HbF levels [20] and was generally well-tolerated during a prolonged treatment period in baboons.…”
Section: Introductionmentioning
confidence: 99%
“…One of the strategies to treat this disease is to reactivate the γ-globin gene that is already present in humans but is silenced during infant development (6–8 months’ birth age). As a result of γ-globin gene activation, the body starts to produce fetal hemoglobin which somehow reduces the blood deficiency in the body [ 3 , 4 ]. Different pharmacological agents have been tested at various stages of clinical trials for their ability to produce fetal hemoglobin [ 5 ].…”
Section: Introductionmentioning
confidence: 99%